Recanalization and Stenting of the Celiac and the Superior Mesenteric Artery Supported by Use of a Steerable Introducer Sheath: Report on 2 Years' Experience. (February 2021) - Pedersoli, Federico; Hitpass, Lea; Isfort, Peter; Zimmermann, Markus; Schulze-Hagen, Maximilian; Gombert, Alexander; Kuhl, Christiane K.; Bruners, Philipp; Keil, Sebastian
Purpose: To compare technical parameters and success of recanalization of celiac (CA) or superior mesenteric artery (SMA) with usage of steerable vs not steerable introducer sheaths. Methods: A retrospective analysis was performed on all consecutive patients who underwent recanalization with stent implantation of CA or SMA between 2015 and 2019. Data regarding technical success (successful stent placement with restoration of sufficient blood flow by the first attempt without changing kind of introducer sheath or access site), indication for treatment, vascular access, kind of introducer sheath, fluoroscopy time and radiation dose were collected. Preinterventional CT were analyzed to classify the difficulty of catheterization of target vessels. Technical parameters were compared with independent t-test (p ≤ 0.05). Results: 66 patients underwent recanalization of CA or SMA. Usage of steerable introducer sheaths was associated with higher technical success compared to not steerable introducer sheaths with transfemoral approach respectively of 8/8 vs 15/19 for the CA and 11/11 vs 17/20 for the SMA. Steerable introducer sheaths were used in recanalization considered more technically difficult compared to not steerable introducer sheaths (58% vs 33%). Usage of steerable introducer sheath showed a statistically significant reduction of radiation dose in the recanalization of the SMA (respectively 32035 ± 15716 cGy cm 2 vs 60102 ± 28432 cGy cm 2 ; p = 0.005). Conclusion: Even if used in more difficult interventions, steerable introducer sheaths showed a higher technical success compared to not steerable introducer sheaths with transfemoral access.